Efektivitas Simulasi Mengajar Pendidikan Pancasila dalam Pengembangan Strategi Pembelajaran Inovatif untuk Kelas 2 SD Negeri Cangkiran 01 - Himathul Aulia Farikha; Aisyah Wardatun Nisa; Eva Nur Hidayah; Kurotul Aeni; Refita Sari (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
The aim of this research is to evaluate the effectiveness of learning simulations in the Pancasila Education subject in implementing creative learning strategies for grade 2 students at SD Negeri Cangkiran 01. This research was conducted using a qualitative descriptive approach, where data collection was carried out through observation, interviews and documentation. The research subjects were 2nd grade teachers and 28 students. The research results show that educational simulations are effective in increasing students' understanding of Pancasila values. This also helps students create more interactive and interesting learning strategies. Demonstrated by better critical thinking skills, better understanding of concepts, and increased student engagement in learning. Educational games based on Pancasila values, stories and role plays are one of the creative learning strategies used. This research shows that educational simulation can be an effective learning alternative in instilling Pancasila values in grade 2 elementary school students at SD Negeri Cangkiran 01.